Desafios e perspectivas do ensino jurídico no século xxi: impactos da evasão na Universidade Federal do Pampa (UNIPAMPA) – campus Santana do Livramento - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This final project examines the challenges facing legal education at UNIPAMPA's Santana do Livramento Campus, focusing on the impacts of student dropout. The main objective is to understand how changes in higher education, particularly curricular guidelines and retention policies, influence academic performance and student dropout rates among law students. A quantitative, exploratory-descriptive methodology is adopted, analyzing UNIPAMPA's internal data on dropout rates (enrollment history, suspensions, and withdrawals) and surveying national statistical indicators. Institutional retention policies (scholarships, student assistance, psychopedagogical support, and curricular innovations) are evaluated. The final outcome is possible recommendations for internal policies to improve curricular development and student support.
Challenges and perspectives of legal education in the 21st century: impacts of dropout at the Federal University of Pampa (UNIPAMPA) – Santana do Livramento campus
Keywords: Evasão universitária; Ensino jurídico; Unipampa; College dropout; Legal education; CIENCIAS SOCIAIS APLICADAS